Controle de condutividade utilizando algoritmos preditivos aplicados à impressão off-set - Diniz, Eber de Castro (2006)
The present work proposes the conductivity control of moisten system applying an predictive algorithm together with the Square Minima Extended. A comparison was accomplished among three predictive algorithms: GPC (Generalized Predictive Control), SPGPC (Smith Preditor Generalized Predictive Control) and SGPC (Stable Generalised Predictive Control), put in the same conditions of numeric parameters, climatic conditions, and using the same identification algorithm, to determine which it is the most suitable for the process of conductivity control.